RELIGION AND LANGUAGE: MULTICULTURAL EDUCATION IN INDONESIA DURING THE COVID-19 PANDEMIC (International Conference on Social and Islamic Studies, 2021)
Multicultural education in the perspective of religion and language contains various characteristics to empower people's peace and freedom in life. During the Covid-19 pandemic. The diversity of religion and language used as a means of community communication  reflects the culture, culture, lifestyle, level of competence of the multicultural education of the speakers. This research focuses on the phenomenon of multicultural education during the COVID-19 pandemic in Indonesia, which shows avariety of religions, languages, and various issues around them, which require attention tobe studied. This study aims to show the findings of the characteristics of community multicultural education in the perspective of religion and language, which often occur and have a wide impact on the nation and religion. This research was conducted with adescriptive qualitative approach, which relies on primary and secondary data collected through electronic media, which were analyzed, reduced, verified, until meaningful research results were found. The results of this study indicate 3 main sub-issues; (1) multicultural education in the perspective of religion and language (diversity of religion & variety of languages); (2) multicultural education in Kindergarten to Higher Education educational institutions is oriented to the values of orientation, equality, and togetherness; (3) the strategy of multicultural education as an effort to avoid conflict, is implemented from the quality of family, school, and community education.